Identification of immunodominant responses to the Plasmodium falciparum antigens PfUIS3, PfLSA1 and PfLSAP2 in multiple strains of mice - Longley, R; Halbroth, B; Ewer, K; Hill, A; Spencer, A (Public Library of Science, 2015)
Malaria, caused by the Plasmodium parasite, remains a serious global public health concern. A vaccine could have a substantial impact on eliminating this disease, alongside other preventative measures. We recently described the development of three novel, viral vectored vaccines expressing either of the antigens PfUIS3, PfLSA1 and PfLSAP2. Each vaccination regimen provided high levels of protection against chimeric parasite challenge in a mouse model, largely dependent on CD8+ T cells. In this study we aimed to further characterize the induced cellular immune response to these vaccines. We utilized both the IFNγ enzyme-linked immunosorbent spot assay and intracellular cytokine staining to achieve this aim. We identified immunodominant peptide responses for CD4+ and CD8+ T cells for each of the antigens in BALB/c, C57BL/6 and HLA-A2 transgenic mice, creating a useful tool for researchers for subsequent study of these antigens. We also compared these immunodominant peptides with those generated from epitope prediction software, and found that only a small proportion of the large number of epitopes predicted by the software were identifiable experimentally. Furthermore, we characterized the polyfunctionality of the induced CD8+ T cell responses. These findings contribute to our understanding of the immunological mechanisms underlying these protective vaccines, and provide a useful basis for the assessment of these and related vaccines as clinical constructs.